Basel Accords and Islamic Banking Regulation: A Bibliometric Analysis of Sharia, Governance, and Capital Adequacy - Elbanna, Mariam; Muthoifin; Nirwana, Andri; Isman (International Journal of Law and Society, 2025)
This study conducts a bibliometric analysis of research addressing the intersection between the Basel Accords and Islamic banking. Using data extracted from the Scopus database covering 2015 to 2024, 1,149 relevant documents were analyzed. A modified PRISMA framework was applied not to assess content quality, but to guide the structured identification, screening, and inclusion of relevant publications, enhancing transparency and reproducibility in the selection process. The analysis used VOSviewer software (v1.6.19) to identify key trends, thematic clusters, and scholarly networks through co-citation, keyword mapping, and co-authorship analysis. The results show that 62% of the literature focuses on Basel III, while only 12% addresses Basel IV, highlighting a lack of academic engagement with the latest regulatory developments. Thematic analysis revealed three dominant research clusters: the impact of Basel III on capital adequacy in Islamic banks,  challenges related to aligning Basel standards with Sharia principles, and the integration of liquidity risk and financial stability within Islamic financial institutions. Malaysia and Indonesia emerged as leading contributors to this field, with a notable rise in publication output from 2020 to 2022, producing over 500 articles. This growth may reflect increased regulatory interest in financial resilience and Islamic finance during and after Covid-19. The study also identifies gaps in the literature, particularly regarding legal harmonization and practical implementation of Basel standards in Sharia-compliant contexts. By mapping the academic landscape, this research offers insights into current trends and future directions, supporting scholars, regulators, and financial institutions.